The World Trade Center Attack: Observations from New York's Bellevue Hospital - Roccaforte, J David (BioMed Central, 2001)
This report describes selected aspects of the response by Bellevue Hospital Center to the World Trade Center attack of 11 September 2001. The hospital is 2.5 miles (4 km) from the site of the attack. These first-hand observations and this analysis may aid in future preparations. Key issues described relate to communication, organization, injuries treated, staffing, and logistics.